Effects of different chicken protein sources on palatability in dry adult dog food - Shields, Chelsie J.; Rozzi, Nicholas L.; Aldrich, Charles G.; Talavera, Martin J. (Frontiers in Animal Science, 2023)
As the demand for dog food production continues to rise, along with the number of dogs per household in the US, sustainable ingredients must be considered for the pet food industry. Consumers have a negative perspective when it comes to animal by-products in their pet’s food. However, animal by-products contribute a quality source of dietary protein, vitamins, and minerals which contribute to nutritionally complete pet foods. Along with being nutritionally complete, foods must also appeal to the dog while eating. The objective of this study was to produce formulas utilizing four different chicken protein sources, and to evaluate the effects of those protein sources on palatability in dogs. Five treatments were produced, through extrusion, using fresh mechanically deboned chicken at two different inclusion levels: (FMDC14 and FMDC25), dried chicken (DC), chicken meal (CM), and chicken by-product meal (CBPM). Four trained panels of twenty-five adult dogs, made up of majority Beagles, randomly divided by sex, were used for palatability testing using the two-bowl test. Based on the palatability results from this study, the CBPM treatment was preferred (p<0.05) over the FMDC14, FMDC25, and DC treatments. The CBPM treatment was at parity to the CM treatment (p>0.05). It can be concluded that the CBPM treatment was considered palatable to the dogs.